The Poetics of Grief: Analyzing the Narrative of Loss and Advocacy in the 'Curhat Bang' Interview with Sharon ‘Timothy Mother’ - Nabila, Bella; Azhari, Jihan; Rosalinah, Yanti (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This article investigates the representation of grief and trauma in Indonesia's digital media landscape, with a particular focus on the role of podcasts as a new space for personal narratives and social advocacy. This study analyzes in-depth an interview with Sharon, the mother of the late Timothy Anugerah Saputra, in a high-profile episode of the podcast